2020
DOI: 10.1021/acs.jpcc.0c05190
|View full text |Cite
|
Sign up to set email alerts
|

From Pyridine Adduct of Borabenzene to (In)finite Graphene Architectures Functionalized with N → B Dative Bonds. Prototype Systems of Strong One- and Two-Photon Quantum Transitions Triggering Large Nonlinear Optical Responses

Abstract: These field dependent molecular properties are of vital scientific and technological importance in the realm of photonics since they govern the non-linear optical behavior of molecules and materials. 18 Based on the above hypothesis and relying on previous experience in nanographene systems, 19,20,21 in this work we open the subject of the non-linear optical properties of PAHs and nanographenes doped with boron nitrogen dative bonds. A dative bond 22,23 denoted in the literature as D→A, is formed between two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
1
7
0
1
Order By: Relevance
“…The coupled perturbed approximation for finite and periodic systems has been applied to calculate static dipole polarizabilities and first hyperpolarizabilities throughout this study. We relied on the Coulomb-attenuating (CAM-B3LYP) functional that provides a good ratio between accuracy and computational efficiency for molecular nonlinear optical properties. , More information about nonlinear optical materials, the quantum-chemical nature of these universal material properties, and the computational methods that are frequently used for their accurate calculation can be found in standard books and articles (see refs , , , and and references therein).…”
Section: Computational Detailsmentioning
confidence: 99%
“…The coupled perturbed approximation for finite and periodic systems has been applied to calculate static dipole polarizabilities and first hyperpolarizabilities throughout this study. We relied on the Coulomb-attenuating (CAM-B3LYP) functional that provides a good ratio between accuracy and computational efficiency for molecular nonlinear optical properties. , More information about nonlinear optical materials, the quantum-chemical nature of these universal material properties, and the computational methods that are frequently used for their accurate calculation can be found in standard books and articles (see refs , , , and and references therein).…”
Section: Computational Detailsmentioning
confidence: 99%
“…[ 47,48 ] Calculations using ab initio and density functional theory (DFT) methods carried out by Karamanis et al suggested that the intermolecular B←N coordination would trigger extra‐strong one‐ and two‐photon quantum transitions followed by intense transfer of charge, which will then significantly alter the absorption profiles of the molecule systems. [ 49 ]…”
Section: Intermolecular B←n Coordinationmentioning
confidence: 99%
“…Some theoretical studies were published on B-N doped PAHs, investigating their possible use as hydrogen storage materials [ 91 ] or on the nature of the intercyclic B-N bond [ 92 ]. Many other research papers on B-N doped PAHs have appeared recently, concerning their applications [ 93 , 94 , 95 , 96 , 97 ], and new structures [ 98 , 99 , 100 , 101 , 102 , 103 ].…”
Section: B-doped Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%